A Sociolegal Perspective to Legal Research in the Digital Field: A Methodological Proposition (Penelitian Hukum Berperspektif Sosiolegal Pada Ranah Digital: Satu Tawaran Metodologis) - Nurtjahyo, Lidwina Inge (UI Scholars Hub, 2021)
Technological developments have brought people, capital, goods, ideas, and even laws into mobility. During the Covid-19 pandemic, technology made mobility possible. Adaptation to pandemic situations occurs by changing physical interactions into interactions in the digital space with the help of technology. These changes also bring consequences to changes in the way of society's law. For example, digital transactions no longer require the presence of a customer or online trials. The challenge that arises then is how to find the method to conduct legal research during the pandemic situation. One of the options presents is socio-legal research conducted digitally. The focal point of this paper as a conceptual article is on methodological issues in studying changes in people's legal ways during a pandemic. This paper aims to offer method options and various legal research topics from a socio-legal perspective in the digital realm.